"Peripheral Neuropathy Crippling Bronchial Asthma": Two Rare Case Reports of Churg-Strauss Syndrome. (16th December 2014) - Pandita, Kamal Kishore; Bhat, Khalid Javid; Razdan, Sushil; Kudyar, R. P.
Abstract : Churg-Strauss syndrome (CSS) is a rare cause of vasculitic neuropathy. Although rare and potentially fatal, Churg-Strauss syndrome (CSS) is easily diagnosable and treatable. The presence of bronchial asthma with peripheral neuropathy in a patient alerts a physician to this diagnosis. This is vividly illustrated by the presented two cases who had neuropathy associated with bronchial asthma, eosinophilia, sinusitis, and positive perinuclear antineutrophil cytoplasmic antibodies (p-ANCA) test, which improved with administration of steroids.